Pragmatic Features of the Use of Emotionally Coloured Expressions in Modern English. Forum for Linguistic Studies - Melnychuk, Natalia (Forum for Linguistic Studies, 2025)
The relevance of the research is determined by the growing role of emotional communication in the digital space, which shapes new approaches to the study of speech practices. The study aims to determine the main types of emotionally coloured statements, their pragmatic functions, and а questionnaire survey, correlation, variance, factor analyses, and their impact on communication. The study employs sampling methods, pragmatic analysis of the text content of social networks, and statistical methods for classifying statements by types, as well as quantitative research of their distribution. The results showed that 60% of emotionally coloured expressions on social media serve for emotional self-expression, and 40% serve for emotional impact on the audience. Only 37.7% of respondents were able to accurately identify the speaker's emotional image, which indicates a significant influence of cognitive factors on the interpretation of messages in the digital environment. The academic novelty lies in the systematic study of the pragmatic functions of emotionally coloured expressions in social networks in English, which reveals the features of their impact on the interaction between authors and their audience, as well as the specifics of their use on different platforms. Further research may include studying the influence of multimedia elements on the emotional colouring of communication in social networks, as well as analysing emotionally coloured expressions in other languages to compare pragmatic features in an interlingual context.
Keywords: Social Networks; Emotional Self-Expression; Emotional Impact; Digital Communication; Pragmatic Functions